A quem pertence o aftermarket automotivo?: práticas anticompetitivas no mercado de reparação veicular brasileiro uma reflexão crítica sobre a jurisprudência do CADE - Diogo Lucas Martins (2017)
The purpose of this study is to reflect on some business practices performed by the Brazilian automotive aftermarket agents and their impacts on competition. The industry under analysis involves a range of relevant markets. In order to delimitate this study, we decided to frame two aspects: (i) the market of automotive parts for repair (the aftermarket, responsible for most of the practices); and (ii) the market of equipment designed to meet the demand of vehicle repairers. The methodological approach is based on the Competition Law, through the examination of three possible practices that may affect free competition in the sector, namely (i) cartel practices complaints involving manufacturers of auto parts; (ii) effects that may arise from vertical restraints of the relationship between automakers and car dealerships in the replacement of original parts; (iii) eventual abuse of intellectual property rights that may result in import barriers for automotive replacement parts. For each practice presented, the decisions of the Conselho Administrativo de Defesa Econômica CADE (Administrative Council for Economic Defense) will be analyzed. Cases involving business practices and its damages or benefits for certain agents that make up the automotive aftermarket chain will be examined. The international experience, especially the European and the North American, will be examined in order to understand such practices and to verify how the vehicle repair sector has reacted to abusive and anticompetitive practices, while seeking solutions and reflections for the Brazilian cases.